GWAS of depression in 4,520 individuals from the Russian population highlights the role of MAGI2 (S-SCAM) in the gut-brain axis - Pinakhina, Daria; Yermakovich, Danat; Vergasova, Ekaterina; Kasyanov, Evgeny; Rukavishnikov, Grigory; Rezapova, Valeriia; Kolosov, Nikita; Sergushichev, Alexey; Popov, Iaroslav; Kovalenko, Elena; Ilinskaya, Anna; Kim, Anna; et al. (Frontiers in Genetics, 2023)
We present the results of the first depression GWAS study involving Russian-descent individuals, which revealed genome-wide significant signal pointing to the novel candidate susceptibility gene - MAGI2. We show that the gene could potentially link inherited risks of depression and irritable bowel syndrome, illustrating how specific genetic susceptibilities for depression could result in the manifestation of systemic symptoms related to psychiatric traits. The genetic analysis provided here highlights the differences between depression phenotypes identified using different diagnostic criteria and indicates potential utility of HADS scale in depression genetic studies.